Collaborative Control of Virtual Formation Trains Based on Event Triggering Mechanism - WEI Wenjing; XIAO Baodi; YUE Lili; LI Maoqing; LIN Junting (Chengshi guidao jiaotong yanjiu, 2024)
［Objective］In order to improve the transportation capacity of railway lines, make the trains form a stable virtual formation within the interval, and reduce the communication pressure during the entire marshaling process, it is necessary to study the collaborative control of virtual formation trains based on the event triggering mechanism. ［Method］The control system of virtual formation trains is introduced, and a method based on the above-mentioned collaborative control is proposed. By analyzing the basic concept of virtual formation trains, a dynamic model of virtual formation trains with disturbance in sections is established, and event triggering conditions are set according to the state error during the train operation using the idea of event triggering, and the distributed controller of the following train is designed. The stability analysis of the control system is carried out based on Lyapunov stability theory, and the effectiveness of the algorithm applied to virtual formation is verified by MATLAB simulation software. ［Result & Conclusion］The designed event triggering function can make the virtual formation system asymptotically stable, and the system has avoided Zeno behavior. Under the action of the controller, the following train can keep the same speed as the lead train within 4 s, while reducing the communication pressure, the entire virtual formation train can also maintain a stable tracking distance.